Promoting positive physical activity behaviors for children and adolescents undergoing acute cancer treatment: Development of the CanMOVE intervention using the Behavior Change Wheel - Grimshaw, Sarah L.; Taylor, Nicholas F.; Conyers, Rachel; Shields, Nora (Frontiers in Pediatrics, 2022)
Background: Increasing participation in physical activity has the potential to improve outcomes for children and adolescents with cancer during treatment and into survivorship. The aim of this study is to outline the theoretical process behind development of CanMOVE, a behaviour change intervention designed to increase physical activity for children and adolescents with cancer. Study design: This study followed a theoretical design process consistent with the Behaviour Change Wheel to inform the design of a complex intervention. Methods: The three stages of the Behaviour Change Wheel intervention design process include: (1) understanding physical activity behaviour within the paediatric cancer setting, (2) identifying potential intervention functions, and (3) identifying appropriate behaviour change and implementation strategies. Qualitative and behaviour change literature relevant to the paediatric cancer treatment setting were used to inform each stage. Results: An individualised and flexible approach to physical activity promotion that considers intrinsic factors specific to the child/adolescent and their environment is required. Fifteen behavioural change strategies were identified to form the intervention components of CanMOVE. Implementation strategies were identified to build motivation, opportunity and capacity towards increasing physical activity behaviours. Key intervention components of CanMOVE include standardised assessment and monitoring (physical activity, physical function, and health-related quality of life), provision of an activity monitor to both child/adolescent and parent, and one-on-one capacity building sessions with a healthcare professional. Capacity building sessions include education, goal setting, an active supervised physical activity session, barrier identification and problem solving, and action planning. Conclusion: CanMOVE is a novel approach to physical activity promotion in the paediatric cancer treatment setting. The use of a theoretical intervention design process will aid evaluation and replication of CanMOVE when it is assessed for feasibility in a clinical setting. The design process utilised here can be used as a guide for future intervention development.